Unravelling the consecutive glycosylation and methylation of flavonols in peach in response to UV‐B irradiation. (13th April 2022) - Xie, Linfeng; Guo, Yan; Ren, Chuanhong; Cao, Yunlin; Li, Jiajia; Lin, Jing; Grierson, Donald; Zhao, Xiaoyong; Zhang, Bo; Sun, Chongde; Chen, Kunsong; Li, Xian
Abstract: Flavonol glycosides are bioactive compounds important for plant defence and human nutrition. Glycosylation and methylation play an important role in enriching the diversity of flavonols in response to the environment. Peach flowers and fruit are rich in flavonol diglycosides such as isorhamnetin 3‐ O ‐rutinoside (I3Rut), kaempferol 3‐ O ‐rutinoside and quercetin 3‐ O ‐rutinoside, and flavonol monoglycosides such as I 3‐ O ‐glucoside and Q 3‐ O ‐galactoside. UV‐B irradiation of fruit significantly induced accumulation of all these flavonol glycosides. Candidate biosynthetic genes induced by UV‐B were identified by genome homology searches and the in vitro catalytic activities of purified recombinant proteins determined. PpUGT78T3 and PpUGT78A2 were identified as flavonol 3‐ O ‐glucosyltransferase and 3‐ O ‐galactosyltransferase, respectively. PpUGT91AK6 was identified as flavonol 1, 6‐rhamnosyl trasferase catalysing the formation of flavonol rutinosides and PpFOMT1 was identified as a flavonol O ‐methyltransferase that methylated Q at the 3 ' ‐OH‐OH to form isorhamnetin derivatives. Transient expression in Nicotiana benthamiana confirmed the specificity of PpUGT78T3 as a flavonol 3‐ O ‐glucosyltransferase, PpUGT78A2 as a 3‐ O ‐galactosyltransferase, PpUGT91AK6 as a 1, 6‐rhamnosyltrasferase and PpFOMT1 as an O ‐methyltransferase. This study provides new insights into the mechanisms of glycosylation and methylation of flavonols, especially the formation of flavonol diglycosides such as I3Rut, and will also be useful for future potential metabolic engineering of complex flavonols.